Peningkatan Kemampuan Bahasa Mandarin Bagi Karyawan Pt. World Innovative Telecommunication (OPPO Smartphone) - Octi Rjeky Mardasari (Universitas Lancang Kuning, 2022)
This community service focuses on training to improve Chinese language skills for employees of PT. World Innovative Telecommunication as a solution offered to the communication constraints between foreign nationals and employees so that employee performance decreases. This training for employees includes language skills training, namely listening, speaking, reading, and writing. In this training, they are taught how to communicate using Chinese daily and are also trained to master Chinese Business. The instructors in this training consisted of Chinese teachers and Indonesian teachers. From the training results obtained, it was seen that the participants were very enthusiastic in participating in the activities carried out, as evidenced by the participants asking several questions and responding actively to the presenters. In addition, there was a significant increase in test results over time, starting from the 1st exam to the final exam. The obstacle faced in this training was ignorance about Video conferences which caused the virtual room to become out of control so that the learning atmosphere was not conducive. Through this short training, it is hoped that employees will be facilitated to increase their knowledge and abilities, which will ultimately impact improving employee performance in doing work.